Grande sonate pour le piano-forte : ... oeuv. 7 par L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Hamburg; Germany; Jean Aug. Böhme, 2022)
Edition of the Piano Sonata no. 4 in E-flat major, op. 7, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page. Plate number 175.